The effects combining cryocompression therapy following an acute bout of resistance exercise on performance and recovery - DuPont, W. H.; Meuris, B. J.; Hardesty, V. H.; Barnhart, E. C.; Tompkins, L. H.; Golden, M. J. P.; Usher, C. J.; Spence, O. A.; Caldwell, L. K.; Post, E. M.; Beeler, M. K.; Kraemer, W. J. (Journal of Sports Science & Medicine, 2017)
Compression and cold therapy used separately have shown to reduce negative effects of tissue damage. The combining compression and cold therapy (cryocompression) as a single recovery modality has yet to be fully examined. To examine the effects of cryocompression on recovery following a bout of heavy resistance exercise, recreationally resistance trained men (n =16) were recruited, matched, and randomly assigned to either a cryocompression group (CRC) or control group (CON). Testing was performed before and then immediately after exercise, 60 minutes, 24 hours, and 48 hours after a heavy resistance exercise workout (barbell back squats for 4 sets of 6 reps at 80% 1RM, 90 sec rest between sets, stiff legged deadlifts for 4 sets of 8 reps at 1.0 X body mass with 60 sec rest between sets, 4 sets of 10 eccentric Nordic hamstring curls, 45 sec rest between sets). The CRC group used the CRC system for 20-mins of cryocompression treatment immediately after exercise, 24 hours, and 48 hours after exercise. CON sat quietly for 20-mins at the same time points. Muscle damage [creatine kinase], soreness (visual analog scale, 0-100), pain (McGill Pain Q, 0-5), fatigue, sleep quality, and jump power were significantly (p < 0.05) improved for CRC compared to CON at 24 and 48 hours after exercise. Pain was also significantly lower for CRC compared to CON at 60-mins post exercise. These findings show that cryocompression can enhance recovery and performance following a heavy resistance exercise workout.